Development of a web-based online cooperative information system - Adamos, Edward A. (2009)
This study aims to design and develop a prototype of the Cooperative Information System. The system aims to provide a facility for cooperative members of the National Confederation of Cooperatives to submit periodic reports through a web-based information system. The system captures the information and is made available for retrieval and viewing.